The associations between health-related physical fitness and fasting blood glucose in war veterans: a population-based study - Mario Kasović; Lovro Štefan; Zvonimir Kalčik (Scientific Reports, 2022)
Abstract The main purpose of the study was to analyze the associations between health-related physical fitness and fasting blood glucose in war veterans. In this cross-sectional study, we recruited 764 men and women aged 45–75 years, who were part of the Homeland War between 1990 and 1995 (33.5% women). Health-related physical fitness included: (1) fat mass and fat-free mass (body composition), (2) push-ups in 30 s (muscular dynamic endurance of upper extremities), (3) sit-ups in 30 s (repetitive upper body strength), (4) chair-stands in 30 s (lower body strength), (5) sit-and-reach test (flexibility) and (6) the 2-min step test (cardiorespiratory function). Laboratory measurement of fasting blood glucose was performed according to standardized procedures in resting seated position after a 12-h overnight fast. Generalized estimating equations with multiple regression models were used to calculate the associations between health-related physical fitness and fasting blood glucose. In men, fasting blood glucose was significantly correlated with fat-free mass (β = − 0.25, p < 0.001), push-ups in 30 s (β = − 0.55, p < 0.001), chair-stands in 30 s (β = − 0.50, p < 0.001), sit-ups in 30 s (r = − 0.45, p < 0.001), the sit-and reach test (r = − 0.46, p < 0.001) and the 2-min step test (r = − 0.19, p < 0.001), while fat mass was positively correlated with fasting blood glucose (β = 0.14, p = 0.004). In women, fasting blood glucose was significantly correlated with fat mass (β = 0.20, p = 0.002), fat-free mass (β = − 0.15, p = 0.014), push-ups in 30 s (β = − 0.49, p < 0.001), chair-stands in 30 s (β = − 0.43, p < 0.001), sit-ups in 30 s (β = − 0.52, p < 0.001), the sit-and reach test (β = − 0.40, p < 0.001) and the 2-min step test (β = − 0.35, p < 0.001). This study shows that fasting blood glucose may be predicted by health-related physical fitness test in war veterans.